Factors and stimuli affecting the conversion of urban and rural places to tourism brands (Study: Guilan province) - habibeh nabi zadeh; Elham Cheraghi; Seyyed Moein Moosavi Nadoshan (تحقیقات کاربردی علوم جغرافیایی)
Considering the factors affecting the conversion of places and destinations to the tourism brand of the prevalence of tourism development in each region. Because these factors play an important role in the conversion of tourism destinations, and on the other hand, the conversion of a destination to its tourism brand is also a factor in developing more tourism in purposes. Considering the importance of this issue, the present study aimed to investigate the factors and stimuli effect on increasing the transformation of urban and rural areas to tourism brand in Guilan province. The present research is in terms of purpose, applied and method of doing it. The data collection tool and the questionnaire and interview information. The statistical population of the research is experts and tourism specialists in Guilan province, using targeted sampling method, 50 experts were selected as samples. To answer the research questions, the binary logistics model and qualitative analysis were used. The results of the research indicate that linear and meaningful communication has existed with the factors and stimuli of the research with the conversion of urban and rural places to the tourism brand. Also, the results showed that among the five factors in question, three factors of diversity of job opportunities, culture and natural assets and local infrastructure have had the most effects on the transformation of urban and rural areas in Guilan province for tourism brand.